2017
DOI: 10.2486/indhealth.2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between occupational and behavioral parameters and oral health status

Abstract: The aim of the present study was to assess the influence of various workplace parameters and oral health behaviors on tooth decay, periodontal disease, and the number of teeth present in industrial workers. The study participants were 1,078 workers (808 males, 270 females, mean age 42.8 ± 11.4 yr) employed at 11 different workplaces. Oral examinations and a self-administered questionnaire were conducted for participants. A logistic regression analysis was conducted to identify factors related to their oral hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 31 publications
(32 reference statements)
3
25
1
4
Order By: Relevance
“…Although a recent Japanese study by Zaitsu et al revealed that occupational status was not significantly associated with the presence of untreated caries among adults 15 ) , our study demonstrates that there is a significant association between occupational status and the presence of untreated caries among female but not among male participants. This discrepancy might be owing to the criteria of occupational status classification.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Although a recent Japanese study by Zaitsu et al revealed that occupational status was not significantly associated with the presence of untreated caries among adults 15 ) , our study demonstrates that there is a significant association between occupational status and the presence of untreated caries among female but not among male participants. This discrepancy might be owing to the criteria of occupational status classification.…”
Section: Discussioncontrasting
confidence: 94%
“…A previous study reported a social inequality in periodontal disease according to occupational status among Japanese males, indicating that skilled workers, sales persons, and drivers had higher risk of developing periodontal disease compared with professionals 14 ) . Another recent study also showed that the subjects in the manufacturing industry and the transport industry were more likely to have tooth loss compared to those in the education and learning support industry 15 ) . However, few studies have focused on the association occupational status and untreated caries.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Few studies have focused on association of socioeconomic status, occupation and educational status to the oral health hygiene. 3,7,8 Thus, exploration of oral health knowledge, attitude and practices can serve to identify the risk factors and thereby help to design behavior modification strategies. 9 Many studies pertaining to oral health status that have been carried out in Nepal mainly target the school-aged children, elderly or pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…An association between job type and oral conditions has also been reported. Some studies have suggested that oral health status may be associated with job classification in Japan 10,11,20,21,35) . Only a few studies have investigated associations between oral conditions and job type, however.…”
Section: Introductionmentioning
confidence: 99%